Hubungan Konten Visual Dengan Tingkat Engagement Pada Brand Fashion - 10080021228, Nauval Fadhil Amrulloh; Yadi Supriadi; Indri Rachmawati (Bandung Conference Series: Communication Management, 2025)
Abstract.Technology helps people get services, The rapid development of technology also influences consumers to make online purchases thus encouraging consumers to move to online stores. Visual content has a very important role in attracting the attention of the audience, This study is aimed to determine the Relationship of Visual Content to the level of engagement in the Jorn Fashion Brand. The method used in this study is a quantitative method with a Correlational Study approach, with a positivistic approach, Data collection techniques using questionnaires involving 90 followers of Jorn selected using the Slovin formula, and interviews with one of Jorn's confidants as secondary data. Data were collected using questionnaires and analyzed with a product moment correlation test. The results of the study showed a correlation coefficient value of 0.865 with a significance of 0.000 which indicates a fairly strong positive relationship between visual content and the level of engagement. This study concludes that there is a relationship between visual content and the level of engagement in fashion brands. Technology helps people get services, The rapid development of technology also influences consumers to make online purchases thus encouraging consumers to move to online stores. Visual content has a very important role in attracting the attention of the audience, This study is aimed to determine the Relationship of Visual Content to the level of engagement in the Jorn Fashion Brand. The method used in this study is a quantitative method with a Correlational Study approach, with a positivistic approach, Data collection techniques using questionnaires involving 90 followers of Jorn selected using the Slovin formula, and interviews with one of Jorn's confidants as secondary data. Data were collected using questionnaires and analyzed with a product moment correlation test. The results of the study showed a correlation coefficient value of 0.865 with a significance of 0.000 which indicates a fairly strong positive relationship between visual content and the level of engagement. This study concludes that there is a relationship between visual content and the level of engagement in fashion brands.Abstrak. Teknologi membantu masyarakat mendapatkan layanan, Pesatnya perkembangan teknologi juga mempengaruhi konsumen untuk melakukan pembelian online sehingga mendorong konsumen untuk berpindah ke online store. Konten visual memiliki peran yang sangat penting dalam menarik perhatian audiens, Penelitian ini ditunjukan untuk mengetahui Hubungan Konten Visual dengan tingkat engagement pada Brand Fashion Jorn. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif dengan pendekatan Studi Korelasional, dengan pendekatan positivistik, Teknik pengumpulan data menggunakan kusioner melibatkan 90 pengikut dari Jorn yang dipilih menggunakan rumus Slovin, dan wawancara kepada salah satu kepercayaa dari Jorn sebagai data sekunder. Data dikumpulkan menggunakan kuesioner dan dianalisis dengan uji korelasi product moment hasil penelitian menunjukan nilai koefisien korelasi sebesar 0,865 dengan signifikansi 0,000 yang mengindikasikan hubungan positif yang cukup kuat antara konten visual dan tingkat engagement. Penelitian ini menyimpulkan bahwa adanya hubungan antara konten visual dan tingkat engagement pada brand fashion.